The Arrows of Time A Debate in Cosmology - Mersini-Houghton, Laura; Vaas, Rudy (Fundamental Theories of Physics, 2012)
The concept of time has fascinated humanity throughout history, and remains one of the biggest mysteries in science and philosophy. Yet a deeper understanding of nature at a fundamental level can only be achieved through a comprehension of this strange fourth dimension. Furthermore, the origin of the universe is closely intertwined with the puzzle of time: Did time emerge at the big bang? Why does the direction of time 'conspire' with the remarkably ordered initial state of the universe?   This book addresses many of the most important questions about time: What is time, and is it fundamental or emergent? Why is there such an arrow of time, closely related to the initial state of the universe, and why do the cosmic, thermodynamic and other arrows agree? These issues are discussed here by leading experts, and each offers a new perspective on the debate. Their contributions delve into the most difficult research topic in physics, also describing the latest cutting edge research on the subject. The book also offers readers a comparison between the different outlooks of philosophy, physics and cosmology on the puzzle of time. This volume is intended to be useful for research purposes, but most chapters are also accessible to a more general audience of scientifically educated readers looking for deeper insights.  .